Manejo do comportamento suicida: proposta de capacitação sob o olhar do enfermeiro - Bomfim, Carlos Henrique dos Reis (2023)
Suicide is a major public health problem, and the nurse who works in the context of primary health care (PHC) is a key player both in approaching the person and his family, as well as in preventing suicide in society. Objectives: To propose training on Suicidal Behavior Management, from the nurse's perspective. Methodology: This is an exploratory, descriptive study of a quantitative-qualitative nature, based on the framework of action research, an active teaching-learning methodological strategy based on the Maguerez Arch to problematize reality. 22 PHC nurses from the municipality of Serra-ES participated. In data collection, questionnaires were used for sociodemographic and work data, Attitude towards Suicidal Behavior (QACS) and programmatic content for the formulation of the Suicidal Behavior Management course for Nurses (MACS-Enf), carried out through pedagogical workshops, followed by a discussion circle. And, in the data analysis, descriptive statistics and content analysis were used, according to Bardin. Results: Of the 22 participating nurses (20 ♀ and 2 ♂); 12 (54.5%) Catholics; and 17 (77.2%) statutory and 77.2% ESF specialists. Our findings show nurses' negative attitudes towards suicide in the three QACS factors - Feelings (mean = 18.7), 2) Perception of professional capacity (mean = 9.03) and 3) Right to suicide (mean = 9.89). Also, the MACSEnf course consists of 9 modules, covering definitions, (pre)concepts, impacts of suicide, mental health promotion, suicide prevention and post-vention. Conclusions: There is a gap in the training of nurses since graduation, which is accentuated by the lack of offerings through permanent education. It is necessary to better prepare nurses to monitor these users in the ESF. It is up to managers to ensure that these users are fully monitored in the health services and, therefore, in the health care network, in particular, the psychosocial care network.